Galactomananas de Parkinsonia aculeata L.: caracterização estrutural e aplicação no isolamento de lectinas ligantes de galactose - Rosa, Ivone Garros (2000)
The affinity chromatography of proteins is baseeiin the specific interaction of these and the matrix. Thus, in order to develop new matrices for the isolation of lectins by affinity chromatography, natural and artificial polysaccharides have been utilized. In this work, the endospermic gums from Parkinsonia aculeata seeels were isolated and fractionated. A family of galactomannans was identifieel, had their structure partially characterizeel and was shown to be composed by four groups of galactomannans. The galactomannans was made by b(l-4) linked linear chain of D-mannose units with d-galactose substitutions in a(1-6), showing relations mannose: galactose of 3.1:1, 3.7:1, 5.0:1 and 6.1:1, corresponding, respectively, to 26.5%, 8.0%, 18.0% and 2.9%, with an insoluble residue of 44.9%. The crude endosperm and the severaI fractions obtaineel from P. aculeata seeds were investigated with respect to their capacity of binding galactose specific lectins. Thus, the polysaccharides were treated with epichlorohydrin and the cross-linked material used as matrices for affinity chromatographic columns, to which lectin rich fractions of Artocarpus incisa, Artocarpus integrifolia and Abrus precatorius seeds were applied. The severaI matrices obtaineel, showeeldifferences in the capacity to interact with the lectins. Thus, ali polysaccharide fractions bound more efficiently the to Artocerpus (A. incisa and A. integrifolia) than to the Abrus precatorius lectins. Moreover, the galactomannan soluble in cold water, which shows a man:gal relation of 3.1:1, was the most efficient for the isolation of the lectins, probably due to the higher number of galactose substitution.